ALIH KODE DAN CAMPUR KODE PADA TUTURAN SISWA KELAS X MIPA 1 SMA NEGERI 4 PONTIANAK - Robi Ramadhan; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2017)
AbstractThis research is motivated because students of class X MIPA 1 SMA Negeri 4 Pontianak including dwibahasawan. In addition, they use of local and Indonesian language still insert other language elements. The purpose of this research to find out the code switching and code mixing on students’ speech of class X MIPA 1 SMA Negeri 4 Pontianak. The method used is descriptive method and qualitative research form. Sources of data in this research are students of class X MIPA 1 SMA Negeri 4 Pontianak which amounted to 40 people, while the data is the result of speech or conversation students. Technique of collecting data used is by sadap technique, simak libat cakap technique, and simak bebas libat cakap technique. The tools used in data collection are the researchers themselves as key instruments and research instruments such as recorder and data recording card. Based on the results of data analysis, there is type of internal code switching and external code switching, type of inner code mixing and outher code mixing, the three factors causing the code switching, and the four factors causing the code mixing on students’ speech of class X MIPA 1 SMA Negeri 4 Pontianak.Keywords: Code Switching, Code Mixing, Students’ Speech